Developing a Thai national critical care allocation guideline during the COVID-19 pandemic: a rapid review and stakeholder consultation - Aniqa Islam Marshall; Rachel Archer; Woranan Witthayapipopsakul; Kanchanok Sirison; Somtanuek Chotchoungchatchai; Pisit Sriakkpokin; Orapan Srisookwatana; Yot Teerawattananon; Viroj Tangcharoensathien (Health Research Policy and Systems, 2021)
Abstract Background At the height of the COVID-19 pandemic, Thailand had almost depleted its critical care resources, particularly intensive care unit (ICU) beds and ventilators. This prompted the necessity to develop a national guideline for resource allocation. This paper describes the development process of a national guideline for critical resource allocation in Thailand during the COVID-19 pandemic. Methods The guideline development process consisted of three steps: (1) rapid review of existing rationing guidelines and literature; (2) interviews of Thai clinicians experienced in caring for COVID-19 cases; and (3) multi-stakeholder consultations. At steps 1 and 2, data was synthesized and categorized using a thematic and content analysis approach, and this guided the formulation of the draft guideline. Within step 3, the draft Thai critical care allocation guideline was debated and finalized before entering the policy-decision stage. Results Three-order prioritization criteria consisting of (1) clinical prognosis using four tools (Charlson Comorbidity Index, Sequential Organ Failure Assessment, frailty assessment and cognitive impairment assessment), (2) number of life-years saved and (3) social usefulness were proposed by the research team based on literature reviews and interviews. At consultations, stakeholders rejected using life-years as a criterion due to potential age and gender discrimination, as well as social utility due to a concern it would foster public distrust, as this judgement can be arbitrary. It was agreed that the attending physician is required to be the decision-maker in the Thai medico-legal context, while a patient review committee would play an advisory role. Allocation decisions are to be documented for transparency, and no appealing mechanism is to be applied. This guideline will be triggered only when demand exceeds supply after the utmost efforts to mobilize surge capacity. Once implemented, it is applicable to all patients, COVID-19 and non-COVID-19, requiring critical care resources prior to ICU admission and during ICU stay. Conclusions The guideline development process for the allocation of critical care resources in the context of the COVID-19 outbreak in Thailand was informed by scientific evidence, medico-legal context, existing norms and societal values to reduce risk of public distrust given the sensitive nature of the issue and ethical dilemmas of the guiding principle, though it was conducted at record speed. Our lessons can provide an insight for the development of similar prioritization guidelines, especially in other low- and middle-income countries.